Faculty Appraisal, Metric Governance, and Dehumanisation in Higher Education - Nomaan, Saima (Journal of Posthumanism, 2024)
This paper examines faculty appraisal systems in higher education as forms of metric governance that operate through socio-technical assemblages rather than neutral evaluative tools. Drawing on a qualitative study of faculty experiences in a Gulf-region higher education context, the analysis reconceptualises student evaluations and managerial appraisals as governing technologies that redistribute power, shape academic labour, and produce dehumanising effects. Rather than locating harm in individual actors, the study foregrounds how metricised appraisal regimes enact performative logics that render faculty visible, comparable, and governable, while simultaneously eroding professional autonomy, recognition, and motivation. Interview data reveal how appraisal metrics function as non-human actors within institutional assemblages, privileging calculability, compliance, and managerial discretion over pedagogical judgement and academic expertise. The paper contributes to posthuman and critical governance debates by theorising faculty appraisal as a mechanism of metric governance that reconfigures academic work, subjectivity, and value within contemporary higher education systems.